Recruitment Analysis Of The Cooperative Labor Force In Improving Human Resources - Luis Marnisah; Syech Idrus; Aisyah; Tabroni (International Journal of Science, Technology & Management, 2021)
Employment recruits of an organization have not improved the standards of selection so that the resulting workforce does not meet the qualifications for the jobs offered. This phenomenon also applies to cooperatives as business organizations. Co-operatives are one of the forums that are quite developed in increasing their business. Currently, the existing human resources are managed simply, the function of personnel management is charged as Manager as the manager of the cooperative. The recruitment process is the earliest stage in personnel management, so if it is ignored it can disrupt the company's performance.The purposes of this study are 1) To find out the labor recruitment process that has been implemented so far. 2) To find out the existing workforce recruitment process. The method used in this research is descriptive qualitative, namely as a research process that produces qualitative data in the form of written or spoken words from the observed person or actor.The results showed that the recruitment process in cooperatives was carried out in a simple but complete and selective manner. The process includes forecasting work needs, selection, an orientation that is still simple but complete enough and based on criteria, standards, or specifications for the real needs of the existing job or position. Recruitment sources are utilized optimally so that professionalism is established. The cooperative uses criteria in the Indonesian economy, namely in the form of workforce skills which include moral and physical health, reason (good knowledge), education and training, work perfection.